Ciência, tecnologia e inovação: interdiscursividade jornalística, reformulação discursiva e heterogeneidades - Pippi, Joseline (2005)
The Green Revolution that took place in the underdeveloped countries in the second half of 20th century has been a propelling mechanism that disseminated new technologies. The media has been compromised, since then, with the news broadcasting of new technologies to the countryside population. However, journalism had to operate as a “translator” of the scientific language, seeking the understanding of audience. This study aims to determine the discoursive translation that occurs between the scientific discourse and the journalistic discourse. Searching the discoursive mechanisms of rewordig the science language for wide open audiences, the research considers the scientific journalism as a discourse builder compromised with determination of a meaning to scientific expressions. Scientific journalism become, in this contexture, a useful discourse-rebuilding tool. Trough news broadcasted in the Zero Hora newspaper, this research analised the discoursive construction of news about genetic modified organisms (GMO’s). Besides, has been determinated the different speeches of individuals about the discourse subject in the press news. The rewording of scientific discourse contributes to create a new inter-discourse that searches the familiarity of the scientific-technical language and constructing a new heterogeneous journalistic interdiscouse.